1980
DOI: 10.7326/0003-4819-92-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis During Continuous Ambulatory Peritoneal Dialysis

Abstract: We initiated a therapeutic program of continuous ambulatory peritoneal dialysis for patients with chronic renal failure. Our program resulted in many episodes of peritonitis arising from contamination due to the technical aspects of the procedure. Microbiologic evaluation showed that 73% of 97 episodes were culture positive, with gram-positive organisms causing most of the cases, especially early in dialysis. Gram-negative rods tended to occur later. Gram stains of dialysate effluent resulted in a disappointin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0
4

Year Published

1980
1980
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(145 citation statements)
references
References 11 publications
3
138
0
4
Order By: Relevance
“…In one study, uninfected patients showed PMN counts of 0 to 40% (mean, 12% ± 2%) whereas infected patients showed PMN counts of 50 to 100% (mean, 85.5% + 2.2%) (39). Occasionally, the number of eosinophils may increase, as in patients with etiologically unclear "eosinophilic peritonitis" (46) (which resolves spontaneously within days to weeks) or fungal peritonitis (3,55,60,128,133), or in those who have had intraperitoneal administration of antibiotics (116). In mycobacterial peritonitis, lymphocytosis is rarely observed (76,101); most dialysates show a predominance of PMNs (67,79).…”
Section: Cell Count and Turbiditymentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, uninfected patients showed PMN counts of 0 to 40% (mean, 12% ± 2%) whereas infected patients showed PMN counts of 50 to 100% (mean, 85.5% + 2.2%) (39). Occasionally, the number of eosinophils may increase, as in patients with etiologically unclear "eosinophilic peritonitis" (46) (which resolves spontaneously within days to weeks) or fungal peritonitis (3,55,60,128,133), or in those who have had intraperitoneal administration of antibiotics (116). In mycobacterial peritonitis, lymphocytosis is rarely observed (76,101); most dialysates show a predominance of PMNs (67,79).…”
Section: Cell Count and Turbiditymentioning
confidence: 99%
“…There is unanimity that the sensitivity of the Gram stain (even on centrifuged samples) and the acridine orange stain (139) is low. Because of the low concentration of microorganisms in the dialysate, tinctorial sensitivity compared with that of culture results has been reported to range only between 10 and 50% (36,68,90,115,116). Gram-positive organisms may have a higher chance of being detected on Gram stain than gram-negative ones (82).…”
Section: Microbiological Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many types of microorganisms may cause PD peritonitis. The most frequent pathogens are Staphylococcus aureus, Gram-positive organisms and S. Epidermidis [4]. A large review of 3366 patients Unauthenticated Download Date | 5/12/18 7:21 AM showed that almost 50% of infections were due to Grampositive organisms and 15% to Gram-negative organisms, 20% were culture negative (sterile peritonitis), only 4% were polymicrobial infections while fungal infection occurred in less than 2% of cases [5].…”
Section: Discussionmentioning
confidence: 99%